Efficacy and safety of Atezolizumab plus Bevacizumab and Lenvatinib as first-line systemic therapies for hepatocellular carcinoma: A real-world study - Sangdao Boonkaya; Chidkamon Pattarawongpaiboon; Panarat Thaimai; Prooksa Ananchuensook; Supachaya Sriphoosanaphan; Suebpong Tanasanvimon; Nattaya Teeyapun; Nussara Pakvisal; Nipaporn Siripon; Sombat Treeprasertsuk; Piyawat Komolmit; Kessarin Thanapirom (PLoS ONE, 2025)
Atezolizumab plus bevacizumab (ATEZO/BEV) and Lenvatinib (LEN) have demonstrated efficacy as first-line systemic therapies for unresectable hepatocellular carcinoma (HCC). This study aimed to compare the efficacy, safety, and outcomes of these two treatments. Data were retrospectively collected from 163 patients with unresectable HCC receiving first-line Lenvatinib (LEN) (n = 85) or ATEZO/BEV (n = 78) between 2020 and 2023 at Chulalongkorn University Hospital in Bangkok, Thailand. The primary outcome was overall survival (OS) following treatment. Propensity score matching (PSM) was used for analysis. The median patient age was 60.6 (SD 11.8) years; 82.2% were male. Most had hepatitis B/C (66.9%), BCLC stage C (73%), and Child-Pugh class A cirrhosis (63.8%). After PSM analysis, overall survival (OS) was significantly longer in the ATEZO/BEV group (12.7 vs. 7.5 months; p = 0.016, HR = 0.618, 95% CI: 0.417–0.916). However, there was no significant difference in progression-free survival (PFS) between ATEZO/BEV and LEN groups (10.8 vs. 7.8 months; p = 0.26, HR = 0.73, 95% CI: 0.431–1.255). Assessed by mRECIST, neither objective response rate (ORR: 23.7% vs. 19.7%, p = 0.555) nor disease control rate (DCR: 36.8% vs. 38.2%, p = 0.867) differed significantly. Multivariate analysis revealed alpha-fetoprotein ≥500 ng/mL (HR = 1.881, 95% CI: 1.028–3.443, p = 0.04), tumor size (HR = 1.833, 95% CI: 1.010–3.327, p = 0.046) and ATEZO/BEV therapy (HR = 0.604, 95%CI: 0.373–0.977, p = 0.04) were independently associated with OS. Adverse event rates were comparable (ATEZO/BEV 43.7% vs. LEN 56.3%; p = 0.08). In conclusion, the study demonstrates that ATEZO/BEV significantly improves OS compared to LEN in patients with unresectable HCC, despite similar PFS, ORR, and DCR. Both treatments have comparable safety profiles.